Normative Review of Direct Regional Head Elections in the Perspective of Constitutional Democracy and the Principle of Shura in Islamic Law - Muhammad Ihsan; Otom Mustomi (Universitas Nurul Jadid, 2025)
This study aims to analyze the mechanism of leadership legitimacy in Indonesia’s direct regional head elections through the perspectives of constitutional democracy and the principle of shura in Islamic law. The critical issues underlying this research include the prevalence of money politics, weak accountability, and the limited application of deliberative values within the modern democratic system, all of which undermine the quality of leadership legitimacy at the regional level. The method employed is library research with a normative approach, utilizing primary legal sources such as Law No. 10 of 2016 on Regional Head Elections and the 1945 Constitution of the Republic of Indonesia, as well as secondary sources on democracy and shura. The analysis is conducted through a comparative and conceptual approach, systematically examining the compatibility between the principles of constitutional democracy and the teachings of shura in Islam. The findings reveal that direct regional head elections represent a manifestation of people’s sovereignty as guaranteed by the constitution, yet remain vulnerable to abuse if not safeguarded by the principles of justice, transparency, and accountability. From the perspective of Islamic law, shura emphasizes deliberation in leadership selection, prioritizing public interest and social justice. Thus, constitutional democracy in the context of regional head elections can be viewed as compatible with the principle of shura insofar as it is implemented based on the values of justice, responsibility, and integrity. This research underscores the importance of integrating constitutional democracy and Islamic values to strengthen participatory and just local governance.